Exploring the effect of transformation leadership on student generic skills: a moderated mediation model - Michael Yao-Ping Peng; Ting Cai; Xiaoyao Yue (Humanities & Social Sciences Communications)
Abstract Topics oriented towards classroom dynamics have garnered considerable attention from the academic community, given the pivotal and illuminating role educators in tertiary institutions embody in facilitating students’ learning processes. This role is particularly crucial in the milieu of the COVID-19 pandemic, a period during which students’ learning engagement is susceptible to being adversely affected due to necessary epidemic prevention and control measures. In light of this, this study aims to explore the impact of teachers’ transformational leadership styles on 483 students’ acquisition of generic skills within classroom settings under the context of institutional degrees of internationalization. The present study meticulously devises a comprehensive set of conceptual frameworks, drawing inspiration from the IEO model. This endeavor aims to empirically substantiate the interrelationships among transformational leadership, self-efficacy, collaborative learning, generic skills, and the degree of internationalization. This study examined the reliability and validity of all variable by the CFA (Confirmatory Factor Analysis) and Partial Least Squares Structural Equation Modeling (PLS-SEM) with BootStrap was employed to calculate the T-valueThe empirical outcomes elucidate that teachers’ transformational leadership has a positive impact on students’ self-efficacy and collaborative learning motivation. Self-efficacy and collaborative learning are important mediating factors in the relationship between teachers’ transformational leadership and students’ generic skills. Self-efficacy and collaborative learning have a positive and significant impact on generic skills and are positively correlated. Self-efficacy not only affects collaborative learning, but also moderates the relationship between transformational leadership and generic skills. The collaborative learning environment promotes the development of basic skills through mutual support and knowledge sharing among students. Notably, the degree of internationalization serves as a positive moderator, enhancing the relationship between transformational leadership, collaborative learning, and generic skills. The study concludes by proffering theoretical and practical implications derived from the research findings, thereby furnishing valuable insights and contributions designed to fortify the existing theoretical foundation.